The Role of Psychological Capital and Organizational Culture in Improving Teacher Innovative Behavior: A Study at Muhammadiyah High School - Pamungkas, Haddad Setyo Ndaru; Mohyi, Achmad; Dewayani, Eka Kadharpa Utama (University of Muhammadiyah Malang, 2024)
In the era of digitalization, innovation in work behavior is increasingly important to support the quality of education. This study aims to examine the effect of psychological capital and organizational culture on the innovative work behavior of SMA Muhammadiyah 2 Sidoarjo teachers either partially or simultaneously. The sample used in this research was 63 teachers at SMA Muhammadiyah 2 Sidoarjo. Primary data was obtained by distributing questionnaires through online surveys using Google Forms. The data analysis method uses multiple linear regression analysis using the SPSS application. The results show that psychological capital has a significant positive influence on innovative behavior and organizational culture. In addition, the combination of these two variables also contributes to the improvement of innovative work behavior. Schools must design development programs to increase teachers' psychological capital and create an innovative organizational culture to encourage creativity and effectiveness in learning.